Information System Design of Web-Based Document Archives Management In The Office Bappeda of North Sumatra Province - Syauqi, Syifa; Suendri, Suendri (Ali Institute or Research and Publication, 2022)
Archives are important documents that are stored with the aim that if they are needed again the archive will be easy to find. Archives have an important role in the Regional Development Planning Agency (BAPPEDA) of North Sumatra Province, so it is hoped that the archive management process is good, fast, and easy. If the archives are not managed properly it will have an impact on the difficulty of finding information and this can hinder the next stage of work. Departing from these problems, a digitalized information system is needed to record these documents. Therefore, archives must be managed with a good and correct management system. This study discusses the design of a document archiving information system according to the needs of the Regional Development Planning Agency (BAPPEDA) of North Sumatra Province based on the system design that has been compiled including use case diagrams, activity diagrams and sequence diagrams. The Regional Development Planning Agency (BAPPEDA) of North Sumatra Province still uses the manual method in managing archives, so with the creation of this system, it is hoped that it can help the work of the Regional Development Planning Agency (BAPPEDA) of North Sumatra Province in terms of archive management. Searching data is also easier and faster because officers or employees do not need to look for archives in books or files listing items that have piled up because they can look at the archive database in the agency.